INTERPRETASI SISTEM SOSIAL PENDIDIKAN ISLAM DITINJAU DARI PERSPEKTIF SOSIOLOGI - ardina zakiya; Binti Maunah (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2022)
The purpose of this study is to describe the sociological view of education and social systems that are included in Islamic education. The method used is the library reserearch method. Data obtained from sources of scientific and theoretical studies. The results of the study can be concluded that: 1) the perspective of sociology in education is related to four perspectives, namely the perspective of evolutionist, functionalist, interactionist and conflict; 2) it is continuous with the history of education and psychology, where psycology views educational phenomena from the point of personal development and sociology looks at the symptoms of education from the point of view of the social structure of society; 3) society and education become a social system related to social stratification; 4) the education system includes several components and education as a system.